2019
DOI: 10.1021/acsomega.9b00789
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Poly(hydroxy urethane)s: Folded-Sheet Morphology and Thermoreversible Adhesion

Abstract: Hybrid poly(hydroxy urethane)s (PHUs) are synthesized by copolymerizing aromatic/alicyclic cyclic carbonates with a polyether amine via addition polymerization. They result into polymers with an average molecular weight of 10 kDa and exhibit solubility in common organic solvents. The hybrid PHUs display T g up to 18 °C. PHUs are enriched with multiple H-bonded interactions and they are assessed using temperature-dependent 1 H NMR and Fourier-transform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The bisphenol A diglycidyl carbonate ( 2b ) is an established precursor for the synthesis of non-isocyanate polyurethanes. ,, Thus, we choose 2b as a model substrate to study the impact of both catalytic systems on the aminolysis of cyclic biscarbonates 2 with 1,4-diaminobutane ( 4 , Table ). Typically, the synthesis of NIPUs is performed in solution e.g., DMSO or extruders .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The bisphenol A diglycidyl carbonate ( 2b ) is an established precursor for the synthesis of non-isocyanate polyurethanes. ,, Thus, we choose 2b as a model substrate to study the impact of both catalytic systems on the aminolysis of cyclic biscarbonates 2 with 1,4-diaminobutane ( 4 , Table ). Typically, the synthesis of NIPUs is performed in solution e.g., DMSO or extruders .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Polyhydroxyurethanes have evolved as one of the few promising sustainable materials to produce urethanes by limiting the use of toxic isocyanates. In some recent studies, the use of CO 2 in synthesizing polyhydroxyurethanes has emerged as an effective way to reduce isocyanate dependency and eliminate 120 million tonnes per year of CO 2 emissions (Nair et al 2019 ). However, polyhydroxyurethane is associated with some limitations related to reaction parameters that can be overcome by using hybrid polyhydroxyurethanes.…”
Section: Bioplastic Precursorsmentioning
confidence: 99%
“…Nair et al 43 described the preparation of thermoreversible hot-melt PHU adhesives based on homo- and copolymers of aromatic, bisphenol A-based, and cycloaliphatic, Araldite CY 230-based, bis(cyclic carbonate)s and aminotelechelic oligo(propylene glycol). 43 Beside the good adhesion values up to 9 MPa on aluminum and 2 MPa on high density polyethylene, the authors showed that the substrates could be debonded manually after thermal treatment up to 100 °C for 0.5 h and then rebonded with no noticeable loss of the shear strength values. Additional examples of hot-melt PHU adhesives may be found in the patent literature and mainly differ by the composition and application/curing temperatures of the thermoplastic.…”
Section: Approaches For the Preparation Of Nipu-based Adhesives And C...mentioning
confidence: 99%
“…Hot-melt PHU adhesives are solvent-free systems that are employed by melting thermoplastic polymers on a heated substrate. Tryznowski et al , fabricated hot-melt PHU adhesives for birch wood. Amino telechelic oligoamides made by the condensation of 1,3-diaminopropane (1,3-DAP) with diethyl tartrate or dimethyl succinate were chain extended with diglycerol dicarbonate providing PHUs containing polyamide segments.…”
Section: Approaches For the Preparation Of Nipu-based Adhesives And C...mentioning
confidence: 99%